2002
DOI: 10.1183/09031936.02.00252402
|View full text |Cite
|
Sign up to set email alerts
|

Imaging in lung cancer: positron emission tomography scan

Abstract: In the past 5 yrs, positron emission tomography (PET), usually used with 18 F-fluoro-2-deoxy-glucose (FDG), has become an important imaging modality in lung cancer patients.Currently, the use of FDG-PET in respiratory oncology is mainly for diagnosis and staging. Standard indications are the evaluation of an indeterminate solitary pulmonary nodule or mass, where FDG-PET has proven to be significantly more accurate than computed tomography (CT) in the distinction between benign and malignant lesions. Several st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
19
0
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 114 publications
0
19
0
2
Order By: Relevance
“…Extrathoracic metastases are reported to be better demonstrated by PET-CT than by either CT or PET alone [67,68]. However, a review of the role of PET in lung cancer imaging [69] stated that indications for PET-CT in NSCLC recurrences needed further prospective investigations. Two studies published in 2010 enrolled 92 and 121 patients who underwent NSCLC resection [70,71] and stated that PET-CT accuracy in assessing intra-and extra-thoracic recurrences was equivalent to or better than standard radiological examinations.…”
Section: Distant Metastasesmentioning
confidence: 93%
See 1 more Smart Citation
“…Extrathoracic metastases are reported to be better demonstrated by PET-CT than by either CT or PET alone [67,68]. However, a review of the role of PET in lung cancer imaging [69] stated that indications for PET-CT in NSCLC recurrences needed further prospective investigations. Two studies published in 2010 enrolled 92 and 121 patients who underwent NSCLC resection [70,71] and stated that PET-CT accuracy in assessing intra-and extra-thoracic recurrences was equivalent to or better than standard radiological examinations.…”
Section: Distant Metastasesmentioning
confidence: 93%
“…As discussed earlier, it is difficult to determine whether a pulmonary lesion presenting in an already treated NSCLC patient represents a recurrence or a second primary tumour [10,20,69] and any new nodule should be properly investigated. Previous studies demonstrated that CT findings of multiple pulmonary nodules with the feeding vessel sign and welldefined and smooth margins in the lower lobes, especially when they were not present on previous images must be suspected of being metastases [69,70,73]. Solitary pulmonary nodules in already treated lung cancer patients may be either recurrent disease or a second primary.…”
Section: Distant Metastasesmentioning
confidence: 99%
“…Ukena · D. HellwigDiagnostik des Bronchialkarzinoms. PositronenEmissions-Tomographie (PET) ZusammenfassungDie Positronen-Emissions-Tomographie mit18 F-Desoxyglukose (FDG-PET) ist ein nichtinvasives Verfahren zum sog. metabolischen "Imaging" des Bronchialkarzinoms.…”
unclassified
“…13,14 Furthermore, it has been shown that Tc-99m methoxy isobutyl isonitrile (MIBI) SPECT faithfully identifies not only the mediastinal lymph node metastases in patients with NSCLCs, 15 but also the chemotherapy response in both small-cell lung carcinoma (SCLC) 16 and NSCLCs. 17 The functional imaging mode of SPECT has a capability to visualize and measure molecular processes in vivo.…”
mentioning
confidence: 99%